2021
DOI: 10.1186/s12935-020-01699-6
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA PIP5K1A promotes the progression of glioma through upregulation of the TCF12/PI3K/AKT pathway by sponging miR-515-5p

Abstract: Background Increasing studies have revealed that circular RNAs (CircRNAs) make great contributions to regulating tumor progression. Therefore, we intended to explore the expression characteristics, function, and related mechanisms of a novel type of circRNA, PIP5K1A, in glioma. Methods Firstly, reverse transcription-polymerase chain reaction (RT-PCR) was carried out to examine CircPIP5K1A expression in glioma tissues and adjacent normal tissues, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…Thus, the identification of valuable biomarkers for early-stage diagnosis and prognosis is crucial for improving the survival of patients with glioma. Recent studies have demonstrated that circRNAs are strongly associated with the clinicopathological characteristics of glioma, and they may serve as diagnostic and prognostic biomarkers ( 32 , 92 , 110 ). Previous studies indicated that the closed-ring structure stabilizes circRNAs in plasma and tissues, and protects them from the enzymatic activity of exonucleases ( 28 , 50 ); therefore, the unique structure of circRNAs may be a potential advantage for their use as biomarkers for the diagnosis and prognosis of glioma.…”
Section: Circrnas and Gliomamentioning
confidence: 99%
“…Thus, the identification of valuable biomarkers for early-stage diagnosis and prognosis is crucial for improving the survival of patients with glioma. Recent studies have demonstrated that circRNAs are strongly associated with the clinicopathological characteristics of glioma, and they may serve as diagnostic and prognostic biomarkers ( 32 , 92 , 110 ). Previous studies indicated that the closed-ring structure stabilizes circRNAs in plasma and tissues, and protects them from the enzymatic activity of exonucleases ( 28 , 50 ); therefore, the unique structure of circRNAs may be a potential advantage for their use as biomarkers for the diagnosis and prognosis of glioma.…”
Section: Circrnas and Gliomamentioning
confidence: 99%
“…Circ-MAPK4 and circ-POSTN were also associated with improved tumor size and WHO grade. Additionally, circPIP5K1A ectopic expression may also be associated with glioma volume and histopathological grade ( 82 ).…”
Section: Expression and Significancementioning
confidence: 99%
“…In addition to FBXW7-185aa described earlier, circ-MAPK4 sponges miR-125a-3p to inhibit glioma cell apoptosis via downregulating P38/MAPK phosphorylation levels ( 44 ). Activation of P38/MAPK is correlated with the apoptosis of nerve cells and tumor cells ( 82 , 83 ).…”
Section: Mechanisms In Glioma Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely accepted that circRNAs usually act as sponges for microRNAs (miRNAs) to participate in various cellular behaviors, including cell proliferation, differentiation, apoptosis and migration, etc., and are even recognized as oncogenes or tumour suppressors [ 6 ]. Among the functional circular RNAs, circPIP5K1A is proposed to facilitate the progression of several cancers, including gastric cancer [ 7 ], ovarian cancer [ 8 ], non-small cell lung cancer (NSCLC) [ 9 ], colon cancer [ 10 ], and glioma [ 11 ]. However, the function of circPIP5K1A in osteosarcoma is not yet identified.…”
Section: Introductionmentioning
confidence: 99%